2020
DOI: 10.1007/s11136-020-02667-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the EQ-5D-5L questionnaire among the general population of Poland

Abstract: Purpose We aim to compare the psychometric properties of the EQ-5D-5L questionnaire with the EQ-5D-3L version and EQ VAS, based on a survey conducted in a sample representing the general adult population of Poland. Methods The survey comprised health-related quality of life (HRQoL) questionnaires: EQ-5D-5L, EQ VAS, SF-12 and EQ-5D-3L, together with demographic and socio-economic characteristics items. The EQ-5D index values were estimated base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 71 publications
3
17
2
Order By: Relevance
“…The present study indicated that the highest and lowest percentage of celling effect was related to self-care and anxiety/depression levels in both of the 3L and 5L, respectively. Our results on celling effect are consistent with studies conducted in Poland 27 and Thailand. 22 A study in Greece 26 found that the highest and lowest proportion of 'no problems' response in both 3L and 5L systems was related to self-care and anxiety/depression which is consistence with our study findings.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The present study indicated that the highest and lowest percentage of celling effect was related to self-care and anxiety/depression levels in both of the 3L and 5L, respectively. Our results on celling effect are consistent with studies conducted in Poland 27 and Thailand. 22 A study in Greece 26 found that the highest and lowest proportion of 'no problems' response in both 3L and 5L systems was related to self-care and anxiety/depression which is consistence with our study findings.…”
Section: Resultssupporting
confidence: 92%
“…Our results for the known-groups validation are consistent with findings of previous studies. [26][27][28] For example, Yfantopoulos and Chantzaras 26 showed that there was higher discriminatory performance of the 5L compared with the 3L version in groups defined by sociodemographic characteristics, except for gender and economic status.…”
Section: Resultsmentioning
confidence: 99%
“…The EQ-5D questionnaire also comprises a Visual Analog Scale (VAS), measuring respondents’ perceived health status, ranging from 0 (the worst thinkable wellbeing) to 100 (the best thinkable wellbeing) [ 29 ]. Specifically, the EQ-5D index value describes the health state, while the EQ-VAS gives information about individual health perception [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review of the literature demonstrated excellent psychometric properties of the EQ-5D across a broad range of populations and conditions [16]. The EQ-5D appears to be reliable and valid in the general population [17][18][19][20][21][22], and so does the SF-6D [23][24][25]. Thus, the reliability and validity of such instruments in the general population are useful for future population health studies.…”
Section: Introductionmentioning
confidence: 99%